2006
DOI: 10.1177/0894439306286852
|View full text |Cite
|
Sign up to set email alerts
|

A Disappearing Digital Divide Among College Students?

Abstract: Given debate about the existence of a digital divide in the United States, the question remains: If individuals are in situations where all have access to the Internet (e.g., a university), will aspects of a digital divide still exist? The authors examine whether a racial digital divide exists among college students in the odds of their using the Internet and the different levels and types of usage. Data are from a random sample of full-time, residential college freshmen. Results indicate that aspects of a dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Men have historically tended to use the Internet more than women which was mostly explained by heightened prior exposure to technology and by work-related requirements (e.g., Cooper, 2006;Cotten & Jelenewicz, 2006;Meraz, 2008;Zillien & Hargittai, 2009). Recently, gender differences in quantity of use have become comparatively small but differences in skill and type of use continue to exist in high diffusion countries (e.g., Dutton et al, 2013;Haight, Quan-Haase, & Corbett, 2014;Van Deursen & Van Dijk, 2015).…”
Section: Socio-cultural Indicators and Digital Engagementmentioning
confidence: 99%
“…Men have historically tended to use the Internet more than women which was mostly explained by heightened prior exposure to technology and by work-related requirements (e.g., Cooper, 2006;Cotten & Jelenewicz, 2006;Meraz, 2008;Zillien & Hargittai, 2009). Recently, gender differences in quantity of use have become comparatively small but differences in skill and type of use continue to exist in high diffusion countries (e.g., Dutton et al, 2013;Haight, Quan-Haase, & Corbett, 2014;Van Deursen & Van Dijk, 2015).…”
Section: Socio-cultural Indicators and Digital Engagementmentioning
confidence: 99%
“…Importantly, the study's gender mix (38 men, 7 women) might have also influenced the results. For instance, Cotten and Jelenewicz (2006) have shown that men and women differ in the ways and regularity with which they use the Internet, and Sax et al (2001) have shown that technological preparedness varies with gender. Future studies should attempt to investigate a wider range of scholars and the factors mediating their participation (e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…Most college students are using the Internet on a daily basis [8], some studies estimate this number to be close to 90% or higher [8,9,10]. However, some questions remain regarding if the use of the Internet by all college students are universal, and that some underrepresented and underprivileged groups are not utilizing the Internet at the same level or for the same purposes [8,9,10,11]. American Indians are increasingly using the Internet [12], though specific numbers are unknown.…”
Section: Introductionmentioning
confidence: 99%